Gambaran Kepemimpinan Yosua dan Implikasinya Bagi Gereja ONKP Jemaat Imanuel Bekasi - Agustinus Waruwu (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
AbstractLeadership is an important role that is able to influence others who become followers. A leader seeks to improve performance at both the individual and group levels or other organizations. Just like Joshua's leadership, it is leadership that gives a picture or success for the Church, especially for the Orahua Niha Keriso Protestant Church (ONKP) of the Immanuel Congregation in Bekasi. The method used in this research is the literature research method.  Related to Joshua's successful leadership, efforts to bring Israel to the place that God has set, when what made Joshua successful as a leader in the midst of the Israelites was not only because of his ability as a human being, but with humility and a good relationship with God, Joshua blessed and also his leadership made successful by God. Thus, the efforts of the Orahua Niha Keriso Protestant Church (ONKP) of the Imanuel Congregation of Bekasi, realizing the success that is the goal for it, so that Joshua's leadership will become the basis for leading and pursuing the success of the ONKP Church of the Imanuel Bekasi Congregation, is growing and even blessed, both in quantity and quality. faith. Keywords:  Leadership, influence, church ONKP, success